Understanding Ethics in Building Workplace Culture: Gender-Based Perspective - Ening Handayani; Wahyudi; Deden Kurniawan (Jurnal Economic Resource, 2022)
This research aims to understand standards of conduct as part of ethics in shaping workplace culture. An exploratory research method is used in this study to analyse the survey result of workplace culture conducted biannually by an international organization in seven provinces in Indonesia. The same data are taken to compare Indonesia with the other seven ASEAN countries: Cambodia, Lao DPR, Malaysia, Myanmar, Philippines, Thailand, and Vietnam to enrich the interpretation of the survey result. The research is to answer two research questions: to what extent standards of conduct as part of ethics influence the workplace culture using gender perspective lens and to find out the most crucial factors in cultivating a conducive working environment.